Factors Influencing Information Security Culture in Organizations Dealing With Economic Crime in Kenya (International Journal of Scientific Research and Management (IJSRM), 2024)
Information security culture is very important for any organization, especially in the public sector, where sensitive information is regularly processed and stored. This importance has become more pronounced in recent years because the frequency and sophistication of cyber-attacks have increased, highlighting the need for effective information security measures such as control policies including access controls, password regulations. However, the success of these measures depends on the development of a strong information security culture within the organization. This study thus aimed to establish the organizational factors influencing information security culture in the organization dealing with economic crime in Kenya. The study focused on information security control, organization structure and organizational culture and how they influence information security culture. The study was underpinned on Security Culture Framework, CIA triad model, structural contingency theory and organizational culture theory. Descriptive research design was adopted. The study targeted 5729 employees in the Economic crimes investigative organizations in Kenya. Stratified random sampling approach was used to classify the sample frame. Simple random sampling technique was utilized to select respondents from each stratum to come up with a sample size of 361 respondents. Data was gathered from the five organizations located in Nairobi County, using self-administered questionnaires. The questionnaires were distributed through a drop and pick-up method, wherein the researcher personally delivered them to the respondents at their workplace. The study produced quantitative data that was coded and entered into Statistical Packages for Social Scientists (SPSS Version 26) for analysis, using both descriptive and inferential statistics. The quantitative data was presented using tables and graphs, with accompanying explanations in prose. The study concludes that information security control has a positive and significant effect on information security culture in five selected state-owned organizations dealing with economic crime in Kenya. In addition, the study concludes that organization structure has a positive and significant effect on information security culture in five-selected state-owned organization dealing with economic crime in Kenya. Further, the study concludes that organizational culture has a positive and significant effect on information security culture in five-selected state-owned organization dealing with economic crime in Kenya. Based on the study findings, the study recommends that the management of state-owned organization dealing with economic crime in Kenya should establish a dedicated and well-defined information security governance structure. This involves creating a specialized information security department or team that reports directly to top management, ensuring that information security is prioritized at the highest organizational level.